Machado de Assis e Luiz Eduardo Frin: literatura em cena - Gallo, Leila Bianca Mélega (2016)
This work investigates fissures between literature and theater, from the dramatization of the story "Missa do Galo", by Machado de Assis. The play, entitled "Missa do Galo", directed by Luiz Eduardo Frin, is part of the Machadianas Project, of Ágora Theatre. The research aims is to: reflect on the dramatization of this machadiano tale; seize, at the play, poetic procedures of modern and contemporary theater scene, as well as analyze the insertion of the epic element on stage. The need of the staging of the modern times in working with devices that do not connect representation to the verisimilitude, led this research to focus on the introduction of narrative expedient in contemporary theater scene, guiding through the following problematization: How far, the staging of play "A Missa do Galo," by Luiz Eduardo Frin, discusses the "theatricality", involving literature and theater? How does the epic and poetic staging live in the staging? The theoretical background concerning the conceptions of contemporary theater scene is mainly supported in the studies of Bertolt Brecht, Anatol Rosenfeld, Peter Szondi, Pierre Sarrazac and Hans-Thies Lehmann. The reasearch is also guided in authors such as Yves Stalloni, Emil Staiger, Roland Barthes and Silvia Fernandes to seize the intrinsic theatricality both in literature and in the staging. Among the final considerations, we emphasize: the play "A Missa do Galo" is not classified as a simple adaptation of Machado de Assis' tale, and it is up to the stage the responsibility to unveil Machado's tale through its dramatization